Bimbingan Teknis Komputer Akuntansi Koperasi Simpan Pinjam untuk Juru Buku Koperasi di Kabupaten Bandung Jawa Barat - Evan Firdaus (LPPM Universitas Koperasi Indonesia, 2023)
The purpose of this accounting computer technical guidance is to assist cooperative financial accounting staff in overcoming the problem of recording savings and loan transactions as a support for obtaining financial information (financial reports) that is faster, more effective, and more efficient by using the software MYOB Accounting. Technical activities begin with the design of cooperative profiles followed by a manufacturing account list, opening balance, tax code, card file, initial loan balance, initial deposit balance, and a general journal. The bookkeepers showed their enthusiasm in implementing the Bimtek Computer for Savings and Loans Accounting because the savings and loan accounting information system uses the software MYOB Accounting can provide financial information effectively and efficiently and assist cooperative finance staff in increasing speed, accuracy, and ease in the process of recording transactions/